Telenovelas in Brazil: From Traveling Scripts to a Genre and Proto-Format both National and Transnational - Straubhaar, Joseph (Global Television Formats: Understanding Television Across Borders, 2012)
In this chapter, we argue that there are several layers of genre, proto-format commercialization of program elements, and current commercially licensed formats. Some genre traditions, like melodrama, tend to be large, over-arching categories that already have a long history before television (Martín-Barbero 1993). Speciﬁc genres of television production, like the U.S. soap opera or the Latin American telenovela can develop within that larger tradition. Even more speciﬁc genres, like the Brazilian socially engaged or historical telenovelas, versus the romantic Mexican Cinderella story telenovela (Hernandez 2001), develop or emerge over time within those genre traditions. Television formats are now often distinguished as a parallel category which looks at forms of television that are packaged for licensing, transfer across cultures, and localized adaptation or implementation by regional, national or local networks. Speciﬁc formats are often imported and adopted. They can feed into genre development, grafted on to older traditions.
Keywords: 1-TV; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Planet TV: A Global Television Reader - Parks, Lisa; Kumar, Shanti (NYU Press, 2003)
From the 1967 live satellite program "Our World" to MTV music videos in Indonesia, from French television in Senegal to the global syndication of African American sitcoms, and from representations of terrorism on German television to the international Teletubbies phenomenon, TV lies at the nexus of globalization and transnational culture. Planet TV provides an overview of the rapidly changing landscape of global television, combining previously published essays by pioneers of the study of television with new work by cutting-edge television scholars who refine and extend intellectual debates in the field. Organized thematically, the volume explores such issues as cultural imperialism, nationalism, postcolonialism, transnationalism, ethnicity and cultural hybridity. These themes are illuminated by concrete examples and case studies derived from empirical work on global television industries, programs, and audiences in diverse social, historical, and cultural contexts. Developing a new critical framework for exploring the political, economic, sociological and technological dimensions of television cultures, and countering the assumption that global television is merely a result of the current dominance of the West in world affairs, Planet TV demonstrates that the global dimensions of television were imagined into existence very early on in its contentious history. Parks and Kumar have assembled the critical moments in television's past in order to understand its present and future. Contributors include Ien Ang, Arjun Appadurai, Jose B. Capino, Michael Curtin, Jo Ellen Fair, John Fiske, Faye Ginsburg, R. Harindranath, Timothy Havens, Edward S. Herman, Michele Hilmes, Olaf Hoerschelmann, Shanti Kumar, Moya Luckett, Robert McChesney, Divya C. McMillin, Nicholas Mirzoeff, David Morley, Hamid Naficy, Lisa Parks, James Schwoch, John Sinclair, R. Anderson Sutton, Serra Tinic, John Tomlinson, and Mimi White.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé